Moderating Effect of Facilitators and Barriers for Purchase of Green Products in India - Laheri, Vishal Kumar (Indian Journal of Marketing, 2020)
The paper aimed to study the influence of factors that enable and inhibit consumers to purchase selected green product categories, that is, organic food products, organic personal-care products, and energy-efficient products. The enabling and inhibiting factors were examined as a moderator between purchase intention and purchase behavior of consumers for green products. Data for the research were collected from 506 Indian consumers. It was found that facilitators (i.e. health, environment friendly, certification, minimum use of pesticides, superior quality, and recyclability) for selected green product categories significantly influenced the purchase intention and purchase behavior of consumers. However, with respect to barriers (i.e. high price, lower availability, lower promotion, lack of certification, lack of well-known brands, resistance to change), it was found that for organic food products and organic personal care products, there was an interaction effect, but for energy-efficient products, there was no significant interaction effect on purchase intention and purchase behavior of consumers for green products. The identified facilitators and barriers for selected green product categories can be helpful for the marketers in minimizing the ‘intention-behavior gap’ among Indian consumers for the purchase of selected green products. The study provides novel insights on the complex buying behavior of Indian consumers for selected green product categories using important variables, that is, facilitators and barriers as moderator between purchase intention and purchase behavior of consumers. The study examined separate models using the process tool for each green product category for both facilitators and barriers for its purchase by consumers.